Enhancing mechanical properties of medium Mn advanced high-strength steel by inter-critical annealing: elimination of austenizing and quenching steps. (25th November 2020) - Zabihi-Gargari, Mohammad; Shahverdi, Hamid Reza; Emami, Mohammad; Askari-Paykani, Mohsen
ABSTRACT: Here, hardenability was enhanced by choosing two different chemical compositions, i.e. the addition of boron (0.12 wt-%) and chromium (2.5 wt-%) to the ordinary composition of the medium Mn advanced high-strength steels (AHSSs). Carbo-boride precipitates were formed in the samples having both boron and carbon in their compositions. Martensite was tempered after intercritical annealing at 700°C. In the alloy with both boron and carbon (A2 alloy), austenite was formed by 2.8 vol.-% after 10-min annealing. Primarily, the annealing process led to the austenite stabilization in the structure of the cold-rolled A2 alloy due to the dissolution of carbo-boride precipitates. For the carbon-free alloy (A1 alloy), on the other, the annealing process and subsequent dissolution of precipitates failed to create austenite stabilization. The resulting mechanical properties for the cold-rolled A2 alloy are ultimate tensile stress of 1029 MPa, total elongation per cent of 19.5 and formability index of 20 GPa%.